Welfare Costs of Inflation in Nepal: An Empirical Analysis - Koirala, T.P. (NRB Economic Review, 2010)
This paper empirically examines the welfare losses arising from the currently rising inflation rate of Nepal using the method introduced into the literature by Bailey (1956) and the demand for real balance function put forward by Deaver (1970). Utilizing annual time series ranging from 1973 to 2009, the result obtained here supports the theoretical underpinning that the rise in inflation is leading to decrease in real balance and hence increase in welfare loss. It is also found that the rate of increases in welfare cost as a result of significant rises in inflation is sluggish. Further, the finding also leads one to conclude that the significant fraction of real income as welfare cost in the year 2010 corresponds to other factors affecting real balance rather than anticipated inflation. However, the evidence is consistent with the view that such cost may change under the relaxation of restrictions imposed corresponding to government’s motivation in raising inflation tax revenue (seigniorage), investment decisions of the economic agents, inflation uncertainty affecting the behavior of money holders and optimal rate of inflation specified.